Revisiting Tamban Beach: Exploring Gender's Influence on Place Attachment and Subsequent Intentions - Purwitasari, Hanifah Wahyu; Dinanti, Dian; Hidayat, Ar Rohman Taufiq (Perencanaan Wilayah dan Kota FT UB, 2025)
This study examines the influence of gender on how tourists' emotional ties to a destination, often referred to as